2023
DOI: 10.3389/fneur.2023.1142642
|View full text |Cite
|
Sign up to set email alerts
|

Multilingual evaluation of interpretable biomarkers to represent language and speech patterns in Parkinson's disease

Abstract: Motor impairments are only one aspect of Parkinson's disease (PD), which also include cognitive and linguistic impairments. Speech-derived interpretable biomarkers may help clinicians diagnose PD at earlier stages and monitor the disorder's evolution over time. This study focuses on the multilingual evaluation of a composite array of biomarkers that facilitate PD evaluation from speech. Hypokinetic dysarthria, a motor speech disorder associated with PD, has been extensively analyzed in previously published stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 82 publications
0
3
0
Order By: Relevance
“…In fact, machine learning (ML) techniques have been developed utilizing various speech and linguistic biomarkers to identify individuals with MCI ( 26 ), early AD ( 27 , 28 ), dementia ( 29 ), Parkinson’s disease ( 30 ), and frontotemporal disorders ( 31 ). For instance, Hajjar and colleagues ( 27 ) found both acoustic and lexical-semantic biomarkers to be sensitive to cognitive impairment and disease progression in the early stages of AD.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, machine learning (ML) techniques have been developed utilizing various speech and linguistic biomarkers to identify individuals with MCI ( 26 ), early AD ( 27 , 28 ), dementia ( 29 ), Parkinson’s disease ( 30 ), and frontotemporal disorders ( 31 ). For instance, Hajjar and colleagues ( 27 ) found both acoustic and lexical-semantic biomarkers to be sensitive to cognitive impairment and disease progression in the early stages of AD.…”
Section: Introductionmentioning
confidence: 99%
“…These limitations are even more pronounced due to the different standardizations used for voice recordings, which include the type of microphone used as well as acoustic conditions 7 . In particular, phonetic variability across different languages imposes considerable practical challenges for developing a unified speech assessment framework 18 . This has motivated the scientific community to explore the possibility of adapting information from different languages to assess certain pathologies 19 , which has raised questions about informational deficits in language-dependent speech dimensions and features 20 .…”
Section: Introductionmentioning
confidence: 99%
“…This has motivated the scientific community to explore the possibility of adapting information from different languages to assess certain pathologies 19 , which has raised questions about informational deficits in language-dependent speech dimensions and features 20 . Indeed, some studies have shown that differences in language did not impact the clinical assessment of disease phenotypes 18 , 21 . Therefore, the development of cross-languages and/or cross-pathology models could be the way to find robust models, with high performance and sufficient generalization for voice-based pathology classification and monitoring.…”
Section: Introductionmentioning
confidence: 99%